KUALITAS PELAYANAN PEMBUATAN KARTU AK-1 BERBASIS ONLINE - Nur Fauziah, Giani; Afrianti, Nia; Agung, Wahyu; Wahyudin, Cecep; Salbiah, Euis (Universitas Djuanda, 2021)
Digital transformation brings significant changes where previously all activity processes used manual methods, now using digital methods. This transformation process must not only be applied to the private sector but to the government sector as well. One of the government sectors engaged in services is the Office of Manpower and Transmigration. This office has one of the programs, which is serving the making of AK-1 cards or job seeker cards. Knowing the Office of Manpower and Transmigration in Kab. Cianjur has carried out a digital transformation in the form of implementing online-based services which has attracted the attention of researchers to examine the quality of implementing this new service system. In this study, researchers used descriptive qualitative methods and data collection techniques for literature studies and observation. The results of this study indicate the quality of online-based AK-1 card-making services at the District Manpower and Transmigration Office. Cianjur is still not good in terms of the tangible dimension, which still lacks facilities in the process of making AK-1 cards. Even on the responsiveness dimension, there is still frequent miscommunication/clarity given by officers to the community. The assurance dimension has also not been implemented optimally, and there are still frequent problems/obstacles in the card-making registration process due to miscommunication and an inadequate online-based registration service system.